POLYMER MELT FLOW IN SUDDEN EXPANSIONS: THE EFFECTS OF VISCOUS HEATING - Zdanski, P. S. B.; Vaz. Jr, M.; Dias, A. P. C. (Revista de Engenharia Térmica, 2008)
Sudden expansion is a typical geometry found at the entrance of a mould cavity and is generally known in industry as ‘gate’. Flow simulation of this class of problems poses some difficulties owing to coupling of momentum and energy laws, existence of re-circulation and steep pressure variations. This work focuses on the physical analysis of the laminar and incompressible polymer melt flow inside channels with sudden expansions aimed at mapping the viscous heating effect. The mathematical model comprises the mass, momentum and energy conservation laws. The pressure-velocity coupling is treated on solving a Poisson equation for pressure. The Cross constitutive model is adopted to describe the non-Newtonian behavior of the flow. The governing equations are discretized using the finite difference method based on central, second order accurate formulae for both convective and diffusive terms. Artificial smoothing terms are added to control the odd-even decoupling problem. The main results demonstrate that the flow parameters, such as pressure drop along the channel and Nusselt number at the walls, are affected by viscous heating. It has been found that, in such problems, any reliable solution must account for the non-isothermal effects.